Causes of greenhouse effect / Sharizet Sumardi - Sumardi, Sharizet (2001)
This literature review on 'Causes of Greenhouse Effect' as a study, due to the lack of information and sources on greenhouse effect especially on the causes. As we know, greenhouse effect, which is energy from the sun heats the earth surface and radiates energy back into space, are one of the major problems to the earth. Human activities that change the chemical composition of the atmosphere through the build up of greenhouse gases include the water vapor, carbon dioxide, methane, chlorofluorocarbons and nitrous oxide are the main causes of the greenhouse effect. With the increasing of these gases in the atmosphere, it gives impacts to the earth and environment. Rising of the sea level and temperature are the main most major impacts of it and there is a lot more impacts due to the increasing of greenhouse gases in atmosphere. Will the earth - the place we live on can be rescued from human activities that cause the destruction mostly in the site of contributing the amount of greenhouse gases to the atmosphere?